Acoustic Wave Sensors for Liquid Environments. (2017) - Caliendo, C.; Hamidullah, M.; Kuznetsova, I.E.; Anisimkin, V.I.; Verona, E.
Abstract: Acoustic wave devices are theoretically investigated in their potential role of technological platform for the development of sensors for liquid environments. In this study, we theoretically studied the propagation of in-plane polarized Lamb modes, Love modes, Shear Horizontal Plate modes along layered structures, aimed at the design of acoustic waveguides suitable to trade-off mass sensitivity and low loss. The phase velocity shift and attenuation due to the presence of a viscous liquid contacting the device surface and to a mass anchored to the sensor surface are calculated for different waveguide structures, confirming that the sensor behavior can be enhanced by a proper choice of the material parameters (i.e., material types, crystallographic orientation, electrical boundary conditions, and thicknesses) of the layered waveguide structure.